Servicio de la Policía Nacional en la parroquia de Guadalupe, Cantón Zamora, Provincia de Zamora Chinchipe y su incidencia en la seguridad ciudadana, año 2022. - Tene Medina, María Belén (2024)
The purpose of this project was to study of the service provided by the national police and its impact on citizen security, it was carried out following the guidelines for the presentation of the Final Report of the Curricular Integration Project of the Public Administration Career, considering each phase of the research process and based on the deductive and synthetic analytical methods pertinent to its scope of action. The general research objective was to diagnose the service provided by the National Police and its impact on citizen security in the Guadalupe parish in 2022. The specific objectives were as follows: to identify the services implemented by the National Police in the Guadalupe parish to ensure the safety of citizens; to determine the limitations faced by the National Police in providing security services to the population of the parish; to propose an improvement plan to foster citizen involvement with the National Police to enhance citizen security. A quantitative approach, combined with exploratory research, was used in the study. A population and a sample totaling 326 residents to be surveyed were also selected. The results show that most people are not informed about the services provided by the National Police despite being an institution responsible for providing security to the parish with a variety of services that in turn is not given 100% compliance by the existence of limitations. Additionally, an improvement plan proposal was achieved, covering different aspects of the objectives for its development.